2018
DOI: 10.1002/jso.24909
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein as a marker of the surgical stress reduction within an ERAS protocol (Enhanced Recovery After Surgery) in colorectal surgery: A prospective cohort study

Abstract: The analysis shows an increase in SIR measured as a CRP value in those patients that had complications. The SIR decreased with laparoscopy in POD1 and POD2 and with ERAS in POD2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The patients’ NRS pain scores were also positively associated with postoperative CRP levels (on POD 1–3) and increase of CRP levels (on POD 2–3). These results not only add to the findings of previous studies that showed CRP level is a clinical marker related to postoperative recovery,12,19 but also show CRP level may reflect postoperative pain outcome.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The patients’ NRS pain scores were also positively associated with postoperative CRP levels (on POD 1–3) and increase of CRP levels (on POD 2–3). These results not only add to the findings of previous studies that showed CRP level is a clinical marker related to postoperative recovery,12,19 but also show CRP level may reflect postoperative pain outcome.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, our findings suggest that a decrease in postoperative CRP levels is closely associated with postoperative pain intensity and opioid requirement of patients. Lastly, minimizing postoperative CRP elevation through more minimally invasive surgical procedures is important to reduce the length of stay12,23 and for lower postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum inflammatory factors, CRP and IL-6 were associated with surgical stress, surgical injury and inflammatory reaction 41 43. This meta-analysis demonstrated that CRP of POD 1, 3/4 and 7 in the ERAS group was lower than in the control group, and there was a significant decrease for IL-6 of POD 1 and 4 compared with the control group.…”
Section: Discussionmentioning
confidence: 73%
“…Higher levels of CRP on postoperative day (POD) 1 was reportedly associated with postoperative complications after gastrointestinal surgery [ 5 , 6 , 13 ]. Furthermore, higher levels of surgical invasion during gastrointestinal surgery increase CRP levels on POD1 [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%